ASSESSING THE REALITY OF THE DIGITAL ECONOMY IN ALGERIA - Abdelli, Razika (The journal of contemporary issues in business and government, 2024)
The world today witnesses continuous changes that would not have occurred without the advancements in the telecommunications and information technology sector, particularly through the internet. This represents a qualitative leap in the concept of modern economy, leading to the emergence of the digital economy. Consequently, all countries have rushed to keep pace with technological advancements to achieve a qualitative leap in digital economy standards on a global level. Today, Algeria faces significant challenges in establishing a foundation capable of keeping up with the times. This study aims to understand the reality of the digital economy in Algeria, analyze and highlight its main features, including aspects such as e-commerce, e-banking, e-government, as well as the challenges it faces.